ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RETURN SAHAM PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING TAHUN 2020-2023 - Balgis, Raissa Zerlina; Wahyuni, Ika; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Transportation companies play a crucial role in moving goods and people from the point of origin to their destination. This research examines the factors influencing stock returns in transportation companies listed on the Indonesia Stock Exchange, with firm value serving as an intervening variable. The study adopts a descriptive quantitative approach. The population consists of transportation companies listed on the Indonesia Stock Exchange between 2020 and 2023, with purposive sampling used to select the sample. Data analysis and hypothesis testing are carried out using Structural Equation Modeling (SEM). Using the Smart PLS 3.0 statistical application, the hypothesis test results indicate that Leverage has a positive impact on Firm Value, Profitability has a positive but not significant effect on Firm Value, and Market Value Added has a negative but not significant effect on Firm Value. Additionally, leverage has a negative and significant impact on stock returns, while profitability has a positive but not significant effect on stock returns, and added market value has a positive but not significant effect on stock returns. Firm Value itself has a positive but not significant effect on Stock Returns. Furthermore, Leverage has a significant positive but not significant effect on Stock Returns through Firm Value, Profitability has a positive but not significant effect on Stock Returns through Firm Value, and Market Value Added has a negative but not significant effect on Stock Returns through Firm Value.